Intertextual infrastructures of modern Arabic fiction:A comparative reading of Naguib Mahfouz’s Midaq alley and ʿAbd al-Rahman Munif’s cities of salt - Almohish, Nouf Rashed Ibrahim (Research Journal in Advanced Humanities, 2026)
This article offers a comparative reading of intertextuality (tanāṣṣ) in the modern Arabic novel through Naguib Mahfouz’s Midaq Alley and ʿAbd al-Rahman Munif’s Cities of Salt. Rather than treating intertextuality as occasional quotation, it approaches it as an organizing principle that structures narrative authority, ethical evaluation, and historical imagination. The theoretical frame combines Arabic critical antecedents (sirqa, iqtibās, taḍmīn, muʿāraḍa) with modern formulations by Bakhtin, Kristeva, and Genette, and it operationalizes intertextuality as a spectrum that includes overt citation, allusive echo, generic inheritance, and discursive borrowing.In Mahfouz, the alley is narrated as an urban palimpsest where Qurʾanic ethical idiom, classical adab, popular storytelling, and the conventions of social realism overlap. These layered voices do not ornament the narrative; they regulate what can be said about desire, respectability, and social mobility, and they turn the alley into a site where competing moral languages collide. In Munif, intertextuality becomes a counter-archival method: oral poetry, local memory, and religious imagery are set against bureaucratic and corporate registers that accompany oil extraction, producing a polyphonic critique of petro-modernity.By placing the two novels side by side, the article argues that intertextuality functions as moral infrastructure in Mahfouz and as political counter-infrastructure in Munif. The conclusion proposes “intertextual infrastructure” as a comparative concept for Arabic fiction across Egypt and the Arabian Peninsula, and it outlines a method for mapping intertextual environments beyond influence-hunting.